Blast Waves - Needham, Charles E. (Shock Wave and High Pressure Phenomena,, 2010)
The primary purpose of this text is to document many of the lessons that have been learned during the author's more than forty years in the field of blast and shock. The writing therefore takes on an historical perspective, in some sense, because it follows the author's experience. The book deals with blast waves propagating in fluids or materials that can be treated as fluids. It begins by distinguishing between blast waves and the more general category of shock waves. It then examines several ways of generating blast waves, considering the propagation of blast waves in one, two and three dimensions as well as through the real atmosphere. One section treats the propagation of shocks in layered gases in a more detailed manner. The book also details the interaction of shock waves with structures in particular reflections, progressing from simple to complex geometries, including planar structures, two-dimensional structures such as ramps or wedges, reflections from heights of burst, and three-dimensional structures. Intended for those with a basic knowledge of algebra and a solid grasp of the concepts of conservation of mass and energy, the text includes an introduction to blast wave terminology and conservation laws as well as a discussion of units and the importance of consistency.